HUBUNGAN TINGKAT KONSENTRASI TERHADAP KETEPATAN MEMANAH - Hardi, Veny Juniarni; Nurama, Dinar (STKIP Pasundan, 2019)
The purpose of this study was to determine the relationship of concentration levels with the accuracy of archery at Moch Idjon Djanbi Archery Club (MIDAC) in Batujajar. The population in this study was 15 people. Given the relatively small population, all members of the population are sampled (total sampling). Data processing was performed using a non-experimental method with a quantitative descriptive approach with a correlational research design. The results obtained are as follows: there is a significant relationship between concentration with archery accuracy of (r = 0.827) where r is the correlation coefficient. Obtained value of Fh (F-count) = 28.207, while the value of Ft (F-table) = 4.67 at a significant level of 0.000 with db (n-k-1) amounted to 4.67. This means that the value of Fh = 28.207> the value of Ft = 4.67. The description shows that the hypothesis that the writer formulated is: